Triangulation Method for Limestone Estimation in CV. Atang Village, Jemparing: Insights from Long Ikis, Paser District, East Kalimantan - Alwi Syahid; Yazid Fanani; Yudho Dwi Galih Cahyono (Journal of Earth and Marine Technology (JEMT), 2023)
The Atang Are Abadi Firm is a limestone mining company that has carried out further exploration activities to determine the volume, density, and continuity of grades in the exploration area. The exploration activities conducted core drilling at 17 drilling points, a distance of less than 250 meters, and an area of 19.36 ha. This research determined the geological domain of limestone layers with parameters of CaO content greater than 53% through a triangulation (triangle) method. Meanwhile, the cut-and-fill method was used for resource and reserve calculations. The resource acquisition in limestone layers with a content of more than 53% reached 25,682,831.9 BCM, and the acquisition of reserves in limestone layers with a content of more than 53% had 6,788,073.56 BCM. The estimation results of limestone resources and reserves obtained based on the Indonesian National Standard 4726: 2019 are included in the classification of measured limestone resources and proven limestone reserves.